Saint Paul a screenplay - Pasolini, Pier Paolo 1922-1975
"Pier Paolo Pasolini's screenplay of an unfinished film about St. Paul is a key addition to the existing bibliography around St. Paul and to a proliferating trend in literature centered on the current turn to religion in philosophy and critical theory. Authors such as Alain Badiou, Slavoj ZiZizek and Giorgio Agamben have all taken part in these discussions. Pasolini's screenplay, however, looks nothing like a sober philosophical treatise on religion, faith or St. Paul; instead, it is a remarkably exciting text, relentless in both its sacralization and profaning of filmic reality"--